The Emerging Role of Platelets in the Formation of the Micrometastatic Niche: Current Evidence and Future Perspectives - Gkolfinopoulos, Stavros; Jones, Robin L.; Constantinidou, Anastasia (Frontiers in Oncology, 2020)
Accumulating evidence suggests that platelets play a key role in cancer metastatic dissemination through their multilevel interaction with tumor cells. Most crucial is the contribution of platelets to the formation and expansion of the early metastatic niche, a protective microenvironment that nurtures the first metastatic cells and is necessary for the establishment of overt metastatic disease. A multitude of mechanisms have been proposed towards this effect. The current review examines the implication of platelets in the three most well-studied mechanisms: (a) the initial preparation of the metastatic microenvironment by the formation of the extracellular matrix (ECM) and the recruitment of granulocytes, (b) the creation of the neovasculature (important for providing the developing tumor with oxygen and nutrients and clearing away the metabolic waste), and (c) the evasion of the immune response by the creation of an immune-suppressive environment around the developing metastases. Finally, the review provides current perspectives on the potential clinical relevance of platelets in cancer progression and their consequent role in cancer therapeutics.